RESEARCH ON THE CONTACT STRESS OF ROLLS AND FATIGUE DAMAGE DISTRIBUTION OF BACKUP ROLL IN FOUR HIGH PC MILL - XU WenBo; QIN XiaoFeng; XU YingJie (Jixie qiangdu, 2020)
The contact fatigue damage of the roll body caused by cyclic contact stress between rolls in four high mill will not only influence the wear of it,but also subsequent grinding and using life. It is of great significance to analyze the distribution of contact stress between rolls under different rolling process parameters for analyzing the damage of rolls and roll maintenance. The finite element method was used to study on the influence of different process parameters on the contact stress distribution and stress distribution uniformity of rolls used in a four high PC mill of 1880 rolling line.The fatigue damage distribution in the axial section of roll body was theoretically calculated by model established based on the damage accumulation theory. The tested fatigue hardening distribution was used to comparing with the theoretical distribution and it is revealed that the theoretical results have some rationality.